An exploratory analysis of implementing an inductive-learning aid in online EFL writing classes: critical reflections for pedagogical implications and practices. (2nd January 2023) - Rungwaraphong, Piyawan
ABSTRACT: This paper presents an exploratory analysis of the implementation of Induction Helper, which is a learning aid created to facilitate and promote Thai students' inductive reasoning ability. Participants were three Thai lecturers of English writing and 45 Thai students. Data was collected through in-depth interviews, projective techniques, and observations of the online training cohorts. Results revealed four features of the Induction Helper that created drawbacks and need further improvement. These include its traditional format, lack of media richness, low interactivity, and inability to facilitate students' conceptualisation of the core principles of business writing. The study recommends modifications to improve these weak features. The results of the study indicate that the Induction Helper has inherent potential and can be upgraded to become a suitable learning resource for online learning.